Morphological and cultural properties of cyanobacterial strains isolated from extreme natural conditions (Experimental biology, 2015)
Obtained аlgological and bacteriologically pure cultures of cyanobacteria Spirulina sp. B12, Synechococcus sp. I12, Synechocystis sp. BT5612, Nostoc sp. B34 isolated from extreme natural areas (hot springTurgen, lake Balkhash, lake Issyk) Kazakhstan. Studied their morphological and cultural properties and set the optimal culture conditions for the isolated strains Synechococcus sp. I12 and Synechocystis sp. BT5612.
Keywords: extreme natural conditions; cyanobacteria